Retrosigmoid Craniectomy for Resection of Epidermoid causing Trigeminal Neuralgia - Amin, Anubhav G.; Wainwright, John V.; Gandhi, Chirag D.; Bowers, Christian A. (Journal of Neurological Surgery Part B: Skull Base, 2019)
The differential diagnosis for trigeminal neuralgia like-symptoms includes cerebellopontine angle lesions causing regional mass effect upon the trigeminal nerve (Fig. 1). Here we present an operative video manuscript of a patient experiencing trigeminal neuralgia, secondary to an epidermoid cyst, in which a retrosigmoid craniectomy was performed to resect the epidermoid and decompress the trigeminal nerve (Fig. 2). This video highlights the operative nuances to achieving a successful surgery, including appropriate patient positioning, dural exposure to the transverse-sigmoid sinus junction, arachnoid dissection, and decompression of cranial nerves. A gross total resection was achieved; the patient reported immediate relief of facial pain postoperatively and has been pain free at the ten month follow-up.The link to the video can be found at: https://youtu.be/Ja2eE0uGk4E.
Keywords: epidermoid cyst; trigeminal; neuralgia; technique